EKSTRAK DAUN Avicennia marina UNTUK MENEKAN AKTIFITAS BAKTERI Vibrio spp. YANG DIISOLASI DARI KEPITING BAKAU (Scylla serrata) SECARA IN VITRO - Mohammad Fadnan Akhmadi; Ery Gusman; Karmila Dewi (Jurnal Harpodon Borneo, 2018)
ABSTRACTAvicennia marina leaf extract is known to suppress the activity of Vibrio spp. using solvent klorform and methanol. Therefore, the authors conducted a further study using different solvents. This research interest determine the ability of extracts of A. marina in suppressing the activity of Vibrio spp. isolated from mud crab (Scylla serrata). A. Marina leaf take in Pantai Amal Lama, The process of extraction, isolation and testing of clear zone performed at the Laboratory of the Faculty of Fisheries and Marine Sciences, University of Borneo Tarakan. Stages of research are: manufacture A. marina leaf extract, isolation, culture of Vibrio spp., and data analysis. The study consisted of 6 treatments, blank control, negative control, positive control, A. marina leaf extract concentration of 15%, 25% and 35%, A. marina leaf extract in each treatment were significantly different (P 0.05). Diameter of clear zone produced at a concentration of 15% obtained an average value of 12.25 ± 5.37 mm, at a concentration of 25% 24.4 ± 1.41 mm, at a concentration of 35% 30.37 ± 0.95 mm. While the positive control 42.5 ± 0:00 mm. But the blank control and negative controls do not form clear zones. Based on these results it can be concluded that there are indications A. marina leaf extract in suppressing the activity of Vibrio spp. were tested in vitro.Keywords: Leaf of A. marina, Vibrio spp., Mangrove crabs (Scylla serrata),                 in Vitro